Interactive Multimedia Effectiveness in Improving Cell Concept Mastery - Rosamsi, Saiman; Miarsyah, Mieke; Ristanto, Rizhal Hendi (FMIPA UNNES, 2019)
The learning process has been carried out in the conventional way, this is caused by the teacher's understanding of using multimedia is still not optimal, so the learning method used is still limited. This phenomenon makes the researchers interested in doing this research. The purpose of the study to determine the effectiveness of multimedia use in improving mastery of cell concepts. this study uses a quantitative approach with a quasi-experimental method. This study uses a quantitative approach with a quasi-experimental method. Based on the results of the study, it was found that the use of interactive multimedia provides a good value of effectiveness in mastering the concept of students cells, compared with learning using conventional media. This is evidenced by the t test on spss obtained value t = 0.00. Based on these results the average value of the gain experimental class is greater, which is 41, compared to the average value of the gain control class, which is 32. The results of this study is indicate there are differences in learning by using interactive multimedia and learning with conventional media. The success of this research can be used by educators in supporting the learning process, especially in biology. Keywords: cell, Interactive Multimedia, Mastery of concepts.